Design Model of Riparian Area of Panjang Island in the Kapuas River - Ratih, Yudhitia; Fibrianto, Jockie Zudhy; Budiarti, Arsanti (Vokasi: Jurnal Publikasi Ilmiah, 2023)
Development of riparian areas based on urban ecology, where there is an ecosystem that is dominated by humans, but still maintains the existing natural system, especially in river riparian green areas. Panjang Island, which is at the mouth of the Kapuas River, is an island that divides the Kapuas River into the Big Kapuas River and the Small Kapuas River. This island has varieties of vegetation in riparian areas that have different and varied characters. So, the varied vegetation patterns in the riparian areas make the water quality different in each zone (Ratih, 2022). The Panjang Island riparian area is an area that is threatened by human activities around it, and with the plan to build the Kapuas III Toll Bridge which will pass through this island, of course there will be a shift in land use functions around the Panjang Island riparian area and also the Kapuas River. This research is a continuation of previous research, where digital identification and mapping was carried out on Panjang Island, namely by developing a concept and making a design model for the Panjang Island riparian area, which still maintains the conservation of the riparian area.